Transformations for Variants of the Travelling Salesman Problem and Applications - Assaf, Mustafa Jamil (2017)
A Master of Science thesis in Engineering Systems Management by Mustafa Jamil Assaf entitled, "Transformations for Variants of the Travelling Salesman Problem and Applications," submitted in April 2017. Thesis advisor is Dr Malick Ndiaye. Soft and hard copy available.